2018
DOI: 10.1002/ad.2343
|View full text |Cite
|
Sign up to set email alerts
|

Co‐produced Urban Resilience: A Framework for Bottom‐Up Regeneration

Abstract: Where the welfare state has failed, can a new civic economy succeed? Constantin Petcou and Doina Petrescu co‐founded atelier d'architecture autogérée to explore participatory urbanism as an answer to today's environmental and economic challenges. One result is R‐Urban, a framework centred around ‘civic hubs’ that allows communities to enhance their resilience through a range of interconnected initiatives. Implemented in neighbourhoods in the Paris area and London, it can be adapted to any location and scaled u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…What is gratifying to see is that the experiences of participants in Colombes are being mirrored in the new R‐Urban sites. Clarisse, who coordinates the activities in the R‐Urban Gennevilliers AgroCité, has observed that: “So far, after one year, there are 252 members, with crazy energy, totally different profiles, to create something that will be a place of learning, transmission around ecology, recycling, and to start living differently, to take care of everything…and so, they [have] changed their way of being a citizen in the city” (Petrescu, Petcou, & Lowe, 2019).…”
Section: Results and Conclusionmentioning
confidence: 99%
See 1 more Smart Citation
“…What is gratifying to see is that the experiences of participants in Colombes are being mirrored in the new R‐Urban sites. Clarisse, who coordinates the activities in the R‐Urban Gennevilliers AgroCité, has observed that: “So far, after one year, there are 252 members, with crazy energy, totally different profiles, to create something that will be a place of learning, transmission around ecology, recycling, and to start living differently, to take care of everything…and so, they [have] changed their way of being a citizen in the city” (Petrescu, Petcou, & Lowe, 2019).…”
Section: Results and Conclusionmentioning
confidence: 99%
“…The subject of our analysis is the first implementation of R‐Urban, a bottom‐up strategy based on networks of urban commons and collective hubs supporting civic resilience practices that was initiated by the activist architecture practice Atelier d'Architecture Autogérée (aaa) (Atelier d'Architecture Autogérée & PublicWorks, 2015; Petcou & Petrescu, 2018; Petrescu, Petcou, & Baibarac, 2016). This first R‐Urban project (2009–16) was established on the suburban outskirts of Paris in Colombes, a multicultural municipality where residents have incomes below the national average and where social housing towers are interspersed with single family dwellings.…”
Section: Introductionmentioning
confidence: 99%
“…Also, historical civilizations throughout the ages were able to preserve their period with its history and content of civilization, its immortal architectural and historical legacy [1]. In one form or another, the sustainability of society can be summed up in "relative multi-centuries preservation" [2,3].…”
Section: Introductionmentioning
confidence: 99%